Hair tourniquet of the uvula - Rahul Dey; M M Zameer; C Vinay; Sanjay Rao (Wolters Kluwer Medknow Publications, 2022)
Hair tourniquet syndrome (HTS) is a condition, where a strand of hair encircles the base of an appendage. We report a rare case of HTS of the uvula and review relevant literature.